2018 AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2018
DOI: 10.2514/6.2018-0569
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Design with Digital Thread

Abstract: Digital Thread is a data-driven architecture that links together information generated from across the product lifecycle. A specific opportunity is to leverage Digital Thread to more efficiently design the next generation of products. This task is a data-driven design and decision problem under uncertainty. This paper explores this problem through three objectives: 1) Provide a mathematical definition of Digital Thread in the context of a specific engineering design problem. 2) Establish the feedback coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…That means CSM and DCSM need to be executed by the same simulation times as SM. Therefore, we compared the total time consumption with the one using the automated (10) From the result, we find that the time-saving rate is 78.1%, meaning less time is needed to implement all the simulations. When the developers design the MDP algorithm in the case study, our MBSE tool-chain captures 14 tool operations (shown in Table V) in order to support automated parameter value selections (e.g., loading model in the simulation tool, generating FMUs).…”
Section: Discussion and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…That means CSM and DCSM need to be executed by the same simulation times as SM. Therefore, we compared the total time consumption with the one using the automated (10) From the result, we find that the time-saving rate is 78.1%, meaning less time is needed to implement all the simulations. When the developers design the MDP algorithm in the case study, our MBSE tool-chain captures 14 tool operations (shown in Table V) in order to support automated parameter value selections (e.g., loading model in the simulation tool, generating FMUs).…”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Second, together with data integration, process management is required to support traceability management of data across the whole lifecycle. Stakeholders access the required data for different parameter configurations and architecture design expected as the digital thread [10]. Third, formalizations of the complex dependencies between architectures and parameter spaces are prerequisite for automated parameter value selection [11].…”
mentioning
confidence: 99%
“…This improved ability for configuration control of project information being digitally available will lead to a preference for model-centric certification, not our current approach for document-centric certification. Several examples include (Zimmerman, 2017;Singh & Willcox, 2018;Mavris, 2018).…”
Section: Modelmentioning
confidence: 99%
“…Wettach et al [7] asserts that the digital transformation sparked by industry 4.0 is meant to be a lot more than a technology-driven change. Over the past few decades, industries have frontloaded their modelling, simulation and design exploration activities with the intention to improve knowledge early-on, make informed decisions already in conceptual stages of the product development process [8] and use this knowledge in manufacturing. Manufacturing plants all over the world, in diverse sectors, are now being upgraded in accordance with industry 4.0.…”
Section: Introductionmentioning
confidence: 99%